AESTHETIC EXPERIENTAL TO VISITOR SATISFACTION AT THE GREEN VALLEY TOURIST PARK IN BANDAR LAMPUNG - Driya Wiryawan; Dwi Asri Siti A; Sherly Noveliza (Jurnal Scientia, 2023)
An understanding of the Aesthetic Experiental is important to be used as a guide for the owners and managers of tourist attractions so as to provide an experience for visitors who visit the tourism park, for this reason the physical things that are in the environment of the Lembah Hijau Tourism Park have an important influence in providing the quality of services provided, so it is necessary to know visitor satisfaction based on the research of Lembah Hijau Tourism Park seen from the concept of Aesthetic Experiential. Therefore, the researcher is interested in conducting a study entitled "Dimensions Aesthetic Experiental on Visitor Satisfaction at the Lembah Hijau Tourism Park in Bandar Lampung". This study aims to determine the effect of dimensions Aesthetic Experiental on visitor satisfaction at the Lembah Hijau Tourism Park in Bandar Lampung. Sampling used in this study was using a non-probability sampling with purposive sampling technique. The number of samples used in this study were 100 respondents. The analysis used is multiple linear regression analysis. The results of the study show that Dimensions Aesthetic Experiental positive and significant effect on visitor satisfaction at Lembah Hijau Tourism Park in Bandar Lampung.